2016
DOI: 10.1007/s00784-016-1750-2
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids as an adjunct for periodontal therapy—a review

Abstract: The host modulatory properties of omega-3 fatty acids warrant further assessment of their use as an adjunct in the management of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 178 publications
1
34
0
6
Order By: Relevance
“…This result may be due to the efforts of the participants to avoid animal products and instead focus on plant sources like flaxseeds or flaxseed oil. Beside the low conversion rate of linoleic acid to EPA and DHA, most clinical successful studies on periodontal inflammation were performed with supplemented EPA and DHA (Chee, Park, Fitzsimmons, Coates, & Bartold, ). Thus, the AID protocol may benefit from an emphasized recommendation for animal sources (e.g., a portion of fatty sea fish like salmon, mackerel, or herring) or supplementation of omega‐3 fatty acids (Brenna, Salem, Sinclair, & Cunnane, ).…”
Section: Discussionmentioning
confidence: 99%
“…This result may be due to the efforts of the participants to avoid animal products and instead focus on plant sources like flaxseeds or flaxseed oil. Beside the low conversion rate of linoleic acid to EPA and DHA, most clinical successful studies on periodontal inflammation were performed with supplemented EPA and DHA (Chee, Park, Fitzsimmons, Coates, & Bartold, ). Thus, the AID protocol may benefit from an emphasized recommendation for animal sources (e.g., a portion of fatty sea fish like salmon, mackerel, or herring) or supplementation of omega‐3 fatty acids (Brenna, Salem, Sinclair, & Cunnane, ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have indicated that dietary supplementation with omega‐3 polyunsaturated fatty acids (precursors of resolvins and protectins) may provide a benefit to the treatment of the disease, especially when combined with aspirin . In this regard, aspirin acetylates and changes the enzymatic function of cyclooxygenase‐2, triggering the production of E‐resolvins from eicosapentaenoic acid and D‐resolvins and protectins from docosahexaenoic acid .…”
Section: Specialized Pro‐resolution Mediatorsmentioning
confidence: 99%
“…Erste klinische Studien konnten bereits den positiven Einfluss einer adjunktiven Einnahme von Omega-3-Fettsäuren zusätzlich zur Parodontitistherapie bezüglich Sondierungstiefenreduktion und Entzündungsreaktion zeigen [29].…”
Section: Merkeunclassified
“…Bei einer vegetarischen oder veganen Ernährungsweise sollte auf eine ausreichende Zufuhr von Vitamin B 12 und Omega-3-Fettsäuren geachtet werden, da ein Mangel dieser Nährstoffe neben allgemeingesundheitlichen auch mit negativen parodontalen Gesundheitskonsequenzen einhergehen kann [29,35].…”
Section: Einfluss Der Proteineunclassified